Аналіз вразливостей безпровідних клавіатур - Черняк, М. А. (ХНУРЕ, 2024)
This work warns about the security risks of wireless keyboards and a hacking method called MouseJack. It highlights the importance for organizations to make sure that employees' wireless keyboards are secure and not vulnerable.
Keywords: безпровідна клавіатура; вразливість безпровідних клавіатур